AB0688 Carotid Intima-Media Thickness in Spondyloarthritis: Prevalence of Subclinical Atherosclerosis in Patients without Clinically Evident Cardiovascular Disease. (10th June 2014) - Alonso Blanco-Morales, E.; Pinto-Tasende, J.; Bejerano, C.; Oreiro, N.; Freire, M.; De Toro, J.; Blanco, F.; Fernandez-Sueiro, J.L.
Abstract : Background: AS and PsA patients without clinically evident cardiovascular disease have a high prevalence of subclinical cardiovascular disease in form of increased carotid intima-media thickness (IMT) and carotid plaques compared to matched controls. Objectives: To evaluate subclinical atherosclerosis by determining carotid IMT and the presence of atheromatous plaques in a sample of patients with PsA and AS, and analyze its relationship with demographic, clinical and analytical characteristics. Methods: Observational and cross-sectional study of 70 spondyloarthritis patients (40 PsA according to the CASPAR classification criteria and 30 AS patients According to the New York classification criteria) were randomly selected from our cohort in 2013. We recorded age and sex of patients, disease duration, joint count, VAS for pain and for global disease activity, BASDAI and BASFI score, ESR, CRP, HLA-B27 and Cw0602, CV risk factors as systolic and diastolic blood pressure, smoking status, glycemia, lipid profile and BMI. IMT (mm) and carotid plaques were measured in the right common carotid artery and the study was performed using high-resolution B-mode ultrasound. Continuous variables were compared using Student's t -test or Mann-Whitney U test. Proportions were compared by chi-square test or Fisher's exact test. Correlation between carotid IMT and continuous variables was tested via estimation of Pearson's partial correlation coefficient adjusted by age at the time of the study. Two-sided P values less than 0.05 were considered to indicate statistical significance. Statistical analysis was performed with the SPSS 17.0 program. Results: Carotid IMT was correlated with age (rho =0.444, p<0.0001), abdominal circumference (r =0.409, p=0.001) and CRP level (r =0.496, p=0.001). Uveitis was associated with higher IMT (0.74 vs 0.62, p=0.046). Also high blood pressure was associated with higher IMT (0.73 vs 0.59, p=0.02). Atheromatous plaques were present in around 10% of patients and were associated with higher IMT (p=0.040). All the other variables were not significantly associated with IMT. Patients with PsA had slightly greater carotid artery IMT than AS (0.67 vs 0.60, p=0.076). Conclusions: In our patients with SAp the carotid intima-media thickness is associated with older age, presence of atheromatous plaques, hypertension, obesity, higher C-reactive protein serum levels and uveitis. References: Gonzalez-Juanatey C, Llorca J, Amigo-Diaz E, Dierssen T, Martin J, Gonzalez-Gay MA. High prevalence of subclinical atherosclerosis in psoriatic arthritis patients without clinically evident cardiovascular disease or classic atherosclerosis risk factors. Arthritis Rheum. 2007 Aug 15; 57(6):1074-80 Gonzalez-Juanatey C, Vazquez-Rodriguez TR, Miranda-Filloy JA, Dierssen T, Vaqueiro I, Blanco R, et al. The high prevalence of subclinical atherosclerosis in patients with ankylosing spondylitis without clinically evident cardiovascular disease. Medicine (Baltimore) 2009; 88: 358–65 Acknowledgements: We wish to express our enormous gratitude to Dr. C Gonzalez-Juanatey Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4712